PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP PEMAHAMAN KONSEP IPA PESERTA DIDIK KELAS VII MTS AL-KHAIRAT BIROMARU - Ardiansyah; Mirnawati; Abdullah, Siti Rahmawati A. Musa (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This education aims to analyse the effect of the Guided Inquiry learning model on the understanding of science concepts of seventh grade students of MTs Al-Khairaat Biromaru. This education has an important role in shaping individuals who are intelligent, characterised, and able to compete in the 21st century era. One of the important skills that need to be developed is science literacy, which not only includes an understanding of scientific concepts but also the ability to think critically and reason in a social context. In the context of science learning at the junior high school level, students' understanding of science concepts is still relatively low, as found in class VII of Mts Al-Khairaat Biromaru. This problem is thought to be related to ineffective learning methods. For this reason, this study aims to determine the effect of the guided inquiry learning model on students' understanding of science concepts. The guided inquiry model involves students actively in the problem-solving process with the support of leading questions from the teacher. This research is expected to contribute to improving the quality of science learning and become a reference for educators in choosing the right method. This research uses a quantitative approach, data collection techniques through observation and tests. The data analysis techniques used are normality test, homogeneity test, and hypothesis testing. The results of this study indicate that the Guided Inquiry learning model at Mts Al-Khairaat Biromaru affects the understanding of science concepts of seventh grade students. The Guided Inquiry learning model is very influential marked by the results of the t test, namely with a significant value of p (0.001) < ? (0.05). This means that Ho is rejected and Ha is accepted so it can be concluded that Ha is accepted which means that there is an effect of guided inquiry learning model on the understanding of science concepts of class VII students of MTs Al-Khairaat Biromaru.